Tahapan Legislasi Perda Wajib Belajar Pendidikan Budaya Alam Minangkabau di Satuan Pendidikan Formal Tingkat Dasar Oleh DPRD Kota Pariaman - Mulia Putri Wijaya (CV. ITTC INDONESIA, 2025)
This study examines the stages of legislation of the Regional Regulation (Perda) on Compulsory Education of Minangkabau Natural Culture in elementary formal education units carried out by the Pariaman City DPRD. The background of this study is the importance of preserving Minangkabau culture through formal education as an effort to maintain the identity and values ​​of local culture amidst the development of the times. The purpose of the study is to analyze the legislative process of the Perda starting from initiation, discussion, to ratification by the Pariaman City DPRD. The method used is a qualitative approach with data collection techniques through documentation studies and interviews with DPRD members and related parties. The findings of the study indicate that the legislative process of this Perda involves the active participation of various elements of society and traditional institutions, and considers Minangkabau cultural values ​​rooted in the philosophy of the traditional basandi syarak-syarak basandi Kitabullah. The implication of this study is that the Perda is not only a legal product, but also an important instrument in preserving culture through education, which can be a model for other regions in integrating local cultural values ​​into the formal education system.